SPAROGRAM: The spatial augmented reality holographic display for 3D visualization and exhibition - Minju Kim; Jungjin Lee; Kwangyun Whon (2014 IEEE VIS International Workshop on 3DVis (3DVis), 2014)
While the 3D graphics technique has found its place for the scientific visualization, especially for medical and biological applications, it has long been speculated that the 3D may not be so much effective as far as the conventional information visualization is concerned. We agree upon this view that the naive extension of the 2D visual forms to 3D is not a way to go. Instead, the computergenerated 3D virtual world will serve best when the virtual world is seamlessly integrated with the real 3D space. For an example, a physical automobile model surrounded with various kinds of virtual visual forms such as texts, images, sounds and 3D models will offer the user (or the audience) another level of appreciation and experience on the subject being presented. In this paper, we present our on-going developmental efforts toward the above framework which calls for the tight integration of the 3D visual forms and the 3D real space. The Spatial AR Hologram (SPAROGRAM) is capable of manifesting augmented three-dimensional information by making full use of the real 3D space that encompasses the surroundings of the real object comprehensively and simultaneously. To accomplish this, a multiple layer of stereoscopic images was implemented. Stereoscopic images enable spatial visualization using the physical and virtual third dimension. Furthermore, ensuring the continuity of the spatial experience, we made the use of spatial exploration with user interaction in real-time. We describe the whole process of system design and prototyping. Our initial investigation suggests that the newly conceived holographic display produce not only continuous 3D space perception, but also the better spatial awareness and realism. Furthermore, it is a promising way to present information in three-dimensional display and help the users understand information effectively and efficiently.